PERTANGGUNGJAWABAN PIDANA PENGATUR LALU LINTAS UDARA SIPIL ATAS KECELAKAAN PESAWAT TERBANG BERDASARKAN UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 1 TAHUN 2009 TENTANG PENERBANGAN - Juan Gunarri G; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The case of aircraft accidents that occurred in Indonesia have seized the attention of the general public , in addition to the adjacent intervals and hit almost all airlines, also highlight the most public attention is the emergence of fatalities in the accident. Public confidence on comfort and safety in the use of air transportation on the wane , although the need for its use is very high . The airline company as the operator , by people considered negligent and unprofessional in the management of the company , on the other hand the Government as the regulator is also considered to be slow in taking action on condition that occurs in the field and do not have the firmness in the provision of airline companies which do not meet safety standardsIn this study the authors, establishes the following principal issues on Criminal Liability Manager Top Air Traffic Accidents Civil Aircraft Based on the Law of the Republic of Indonesia Number 1 Year 2009 on Flight well as deeds whether that included the scope of criminal offenses in the field of aviation in the perspective of Law -Undang Republic of Indonesia Number 1 Year 2009 on FlightsWriting is when viewed from the type of research that is classified as a normative legal research is research conducted by examining the legal library materials related to the problems , whereas when viewed from nature , this research is descriptive research that explains in clear form sentences and detail.From the research that the Criminal Liability of Civil Air Traffic Manager Top Aircraft Accidents can be charged to the Air Traffic Manager that caused a plane crash with the provisions can be demonstrated that the main cause of the accident because there are factors intent , recklessness , or negligence committed by the Governing air Traffic , whereas acts falling within the scope of criminal offenses in the field of aviation was purposely fly and operate aircraft which endanger the aircraft and during the flight do anything that could jeopardize flight safety and security .Keywords: Accountability - Air Traffic Manager